Deficiency of sphingomyelin synthase 2 prolongs survival by the inhibition of lymphoma infiltration through ICAM‐1 reduction. Issue 3 (22nd January 2020) - Taniguchi, Makoto; Ueda, Yoshibumi; Matsushita, Michiko; Nagaya, Shingo; Hashizume, Chieko; Arai, Kenta; Kabayama, Kazuya; Fukase, Koichi; Watanabe, Ken; Wardhani, Lusi Oka; Hayashi, Kazuhiko; Okazaki, Toshiro
ABSTRACT: The tumor microenvironment (TME) formation involving host cells and cancer cells through cell adhesion molecules (CAMs) is essential for the multiple steps of cancer metastasis and growth. Sphingomyelin synthase 2 (SMS2) is involved in inflammatory diseases such as obesity and diabetes mellitus by regulation of the SM/ceramide balance. However, the involvement of SMS2 in TME formation and metastasis is largely unknown. Here, we report that SMS2‐deficient (SMS2‐KO) mice show suppressed the EL4 cell infiltration to liver and prolonged survival time. ICAM‐1 was identified as a candidate for the inhibition of TME formation in immortalized mouse embryonic fibroblasts (tMEFs) from mRNA array analysis for CAMs. Reduced SM/ceramide balance in SMS2‐KO tMEFs suppressed the attachment of EL4 cells through transcriptional reduction of ICAM‐1 by the inhibition of NF‐κB activation. TNF‐α‐induced NF‐κB activation and subsequent induction of ICAM‐1 were suppressed in SMS2‐KO tMEFs but restored by SMS2 re‐introduction. In the EL4 cell infiltration mouse model, EL4 injection increased ICAM‐1 expression in WT liver but not in SMS2‐KO mouse liver. Therefore, inhibition of SMS2 may be a therapeutic target to suppress the infiltration of malignant lymphoma.